Evaluation of the reality of letters of guarantee in light of the application of the electronic platform in the Iraqi environment:: (An Applied research) (Journal of Accounting and Financial Studies ( JAFS ), 2022)
The research aims to identify the letters of guarantee importance as an electronic supervisory control that manages letters of guarantee issuance and puts an end to fraud and manipulation operations, in addition to identifying the reasons that led to the use of letters of guarantee in Iraqi banking environment in the first place.The research problem was marked in one major wonderment is that to what extent may the electronic platform limits the risks of guarantee letters?The research solved occurred problems relying on connection and effect hypotheses, the first connection hypotheses represented as follows:There is no connection relation that has significant statistics between traditional guarantee letters in its dimensions X and limiting guarantee letters risks, second; there is no connection relation that has significant statistics between traditional guarantee letters in its dimensions Z and limiting guarantee letters risks beyond the electronic platform.While the main first effect hypotheses: There is no effect that has significant statistics between traditional guarantee letters in its dimensions X in limiting Y guarantee letters risks, and the second hypotheses; there is no effect that has significant statistics between traditional guarantee letters in its dimensions Z and limiting Y guarantee letters risks beyond the electronic platform.Thus, the researcher has reached a set of results and the most important ones were: The weakness of decision centralization and followed procedures to issue guarantee letters before the platform has contributed in increasing guarantee letters risks, and the guarantee letters issued by the platform are considered in match with Iraqi trade law number (30) for the year 1984 and the central bank of Iraqi decisions and international customs. In addition, the letters of guarantee platform has contributed widely in preserving benefactors’ rights due to electronic supervisory control, and the recommendations to improve the platform and working on creating a new field in the platform and to develop it in wider fields by connecting the client’s account to the platform in order to support the financial inclusion operations, furthermore, guarantee letters documents and especially real-states that are being pawned should include an electronic issuance certification with the availability of sophisticated means to unveil any fraud that may occurs, which promotes the use of technology widely in the governments’ directories and electronic supervisory to achieve electronic governance.